The Scholarship of 'Cults' and the 'Cult' of Scholarship - James R. Lewis (Journal of Dharma, 1987)
The following pages will undertake a critique of the academic enterprise as it manifests in the study of new religious movements, although it is also, by implication, simultaneously a critique of secular scholarship more generally. My objections to new religion scholarship can be condensed to the observation that most of the literature in the field-whatever its other merits-frequently has the effect of increasing the sense of the alienness and the otherness of alternative religious groups (thus inadvertently reinforcing rather than undermining popular "cult" stereotypes). Conversely, I want to make the case for a humanistic style of scholarship which, at least as a preliminary move, attempts to give one access to the lifeworld and to the deeper intentionality of the new religions.